ANOTHER DIMENSION OF COMMUNICATION “EXAMPLE OF METAVERSE IN THE VIRTUAL WORLD” - LOKMANOĞLU, Ensar (SSD Journal, 2022)
Starting from the 1990s with the birth of the Internet, the development of social networks, augmented reality applications and digital transformation from the real world to the virtual world today have developed in many areas. These developments in the virtual universe have gained great importance recently as they enable real and legal persons to interact on digital platforms. The digitalization process that started with web 1.0, which we perceive as reading what is written on the internet, was followed by producing content with Web 2.0, and even bloggers, youtubers, influencers became widespread in this period. With Web 3.0, a decentralized platform is aimed without any intermediaries (Twitter, Facebook, Instagram, etc.). With this development, a virtual but also a real universe was born that not only makes use of the internet, but also offers the opportunity to live in the internet. People choose the most suitable one among these universes, which is called the metaverse, consisting of the combination of the words "meta" and "universe", and combine different technologies in the internet environment to buy land, shop, play games, make their own designs and socialize. Over time, individuals who grow up on the Internet are formed, and these "digital natives" will become the businessmen, teachers, lawyers, doctors of the future and will transfer these technological innovations to their lives throughout their lives. Metaverse, called augmented reality with XR Technology, is a computer-based and wearable technology. For this reason, the tools used to implement the metaverse world should be light, easy to access and portable, and the person who will use this system should have technological knowledge In this study; Metaserve, which came into our lives through the developments in information processing technologies and digital avatars, provides a virtual culture in social relations and communications, apart from evaluating it as an active and enjoyable leisure time. It is evaluated that it causes malfunctions and solutions are offered to minimize them.